2020
DOI: 10.3389/fnbot.2020.00015
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Toward Subject-Specific Gait Rehabilitation Through Single-Joint Resistive Force Interventions

Abstract: Walking is one of the most relevant tasks that a person performs in their daily routine. Despite its mechanical complexities, any change in the external conditions that applies some external perturbation, or in the human musculoskeletal system that limits an individual's movement, entails a motor response that can either be compensatory or adaptive in nature. Incidentally, with aging or due to the occurrence of a neuro-musculoskeletal disorder, a combination of such changes including reduced sensory perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Reducing knee loading as an alternative for knee osteoarthritis treatment was proposed as one example application. Other potential applications could be studied with minimal changes such as gait retraining to prevent running injuries [41] and gait rehabilitation [42], [43]. This study validated the mapping-based dosage selection method for two gait parameters.…”
Section: Discussionmentioning
confidence: 61%
“…Reducing knee loading as an alternative for knee osteoarthritis treatment was proposed as one example application. Other potential applications could be studied with minimal changes such as gait retraining to prevent running injuries [41] and gait rehabilitation [42], [43]. This study validated the mapping-based dosage selection method for two gait parameters.…”
Section: Discussionmentioning
confidence: 61%
“…The MDC has been used to determine clinical significance for changes in poststroke gait, and thus these results suggest the feasibility of the resistive exosuit paradigm for increasing plantarflexor effort in people poststroke. Another recent study found that in the presence of plantarflexor resistance, healthy individuals reduced ankle joint range of motion and peak plantarflexion angle [ 32 ]. While our findings are consistent with these outcomes, we observed only slight reductions in peak plantarflexion angle (2–4°) when applying up to 300 N of force compared to the approximately 10° seen in prior work when applying 10 N [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 B). One-minute subdivisions were chosen as this is a common timeframe for analysis in exosuit work [ 32 , 50 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations